How the State Criminalizes Immigrants and to What Effect: A Multidisciplinary Account. (August 2019) - Garip, Filiz; Gleeson, Shannon; Hall, Matthew
The recent salience of immigration as an issue has led to more restrictive policies toward immigrants in many settings. This special issue brings together scholars from multiple disciplines and presents a collection of articles that investigates the nature of immigration enforcement, examines the actors and institutions involved, and uncovers some of the consequences for immigrants and communities. This introductory article takes stock of the main findings and makes a case for future work to (a) include multiple sites and units of analysis, (b) consider the perspectives of on-the-ground enforcement agents, and (c) integrate the study of immigration enforcement to other subfields within and across disciplines.